Influence of sustainable use of environmental goods and services on the green economy goals in African countries (2013)
This paper reviewed the status of environmental goods and services utilization in Africa viz-a-viz the goal of green economy. A systematic appraisal of the potential of utilizing forest goods and services in a sustainable manner to reduce the striking poverty in Africa is one of the focuses of this paper. It identified the challenges slowing down the development of environmental goods and services in a sustainable manner to guarantee green economy in Africa. The paper recommends urgent action in the direction of poverty and ignorance reduction by governments in Africa. This will engender sustainable utilization of goods and services in African states' indigenous communities towards meeting the green economy goals.